Man and superman - Eaton, Lynn (BMJ Group, 2003)
Christopher Reeve—“Superman”—is rarely out of the limelight since a riding accident left him severely disabled. Certainly his fame—and fortune—have helped him deal with his disability, but his apparent emphasis on the importance of walking has outraged the disability lobby